Visual outcomes after anterior temporal lobectomy and transsylvian selective amygdalohippocampectomy: A quantitative comparison of clinical and diffusion data. Issue 3 (12th January 2023) - Pruckner, Philip; Nenning, Karl‐Heinz; Fischmeister, Florian Ph.S; Yildirim, Mehmet‐Salih; Schwarz, Michelle; Reitner, Andreas; Aull‐Watschinger, Susanne; Koren, Johannes; Baumgartner, Christoph; Prayer, Daniela; Rössler, Karl; Dorfer, Christian; et al.
Abstract: Objective: Anterior temporal lobectomy (ATL) and transsylvian selective amygdalohippocampectomy (tsSAHE) are effective treatment strategies for intractable temporal lobe epilepsy but may cause visual field deficits (VFDs) by damaging the optic radiation (OpR) . Due to the OpR's considerable variability and because it is indistinguishable from surrounding tissue without further technical guidance, it is highly vulnerable to iatrogenic injury. This imaging study uses a multimodal approach to assess visual outcomes after epilepsy surgery. Methods: We studied 62 patients who underwent ATL ( n  = 32) or tsSAHE ( n  = 30). Analysis of visual outcomes was conducted in four steps, including the assessment of (1) perimetry outcome (VFD incidence/extent, n  = 44/40), (2) volumetric OpR tractography damage ( n  = 55), and the (3) relation of volumetric OpR tractography damage and perimetry outcome ( n  = 35). Furthermore, (4) fixel‐based analysis (FBA) was performed to assess micro‐ and macrostructural changes within the OpR following surgery ( n  = 36). Results: Altogether, 56% of all patients had postoperative VFDs (78.9% after ATL, 36.36% after tsSAHE, p  = .011). VFDs and OpR tractography damage tended to be more severe within the ATL group (ATL vs. tsSAHE, integrity of contralateral upper quadrant: 65% vs. 97%, p  = .002; OpR tractography damage: 69.2 mm 3 vs. 3.8 mm 3, p  = .002). Volumetric OpR tractography damage could reliably predict VFD incidence (86% sensitivity, 78% specificity) and could significantly explain VFD extent ( R 2  = .47, p  = .0001). FBA revealed a more widespread decline of fibre cross‐section within the ATL group. Significance: In the context of controversial visual outcomes following epilepsy surgery, this study provides clinical as well as neuroimaging evidence for a higher risk and greater severity of postoperative VFDs after ATL compared to tsSAHE. Volumetric OpR tractography damage is a feasible parameter to reliably predict this morbidity in both treatment groups and may ultimately support personalized planning of surgical candidates. Advanced diffusion analysis tools such as FBA offer a structural explanation of surgically induced visual pathway damage, allowing noninvasive quantification and visualization of micro‐ and macrostructural tract affection.